تمويل التنمية الاجتماعية عبر إصدار الصكوك الإسلامية في أفغانستان: استلهاما من التجربة الماليزية: Financing Social Development through the Issuance of Sukuk in Afghanistan: Inspired by the Malaysian Experience - Heravi, Farid Ahmad; Sharofiddin, Ashurov (International Journal of Al-Turath In Islamic Wealth and Finance, 2024)
الملخص تهدف هذه الدراسة إلى تقديم اقتراح تمويلي يبرز دور الصكوك الإسلامية كأداة فعالة في تمويل التنمية الاجتماعية، بما في ذلك مجالات التعليم والرعاية الصحية ومشاريع البنية التحتية. تسهم هذه الأداة في تعزيز التنمية الاقتصادية، وخلق فرص العمل، والحد من الفقر والبطالة. وفي هذا السياق، تحتاج أفغانستان، كونها دولة فقيرة، إلى إصدار الصكوك لتمويل التنمية الاجتماعية، مستفيدة من التجربة الماليزية الناجحة في هذا المجال. وتعتبر التجربة الماليزية في تطوير قطاع الصكوك لتمويل التنمية الاجتماعية من أنجح التجارب على مستوى العالم، وذلك بفضل عدة عوامل، منها دعم الحكومة، وجذب المستثمرين المحليين والدوليين، وتوفر إطار قانوني وتنظيمي للصكوك، بالإضافة إلى وجود هيئة رقابة شرعية مستقلة. وقد أصدرت ماليزيا أنواعًا متعددة من الصكوك لتمويل التنمية الاجتماعية. واستخدم الباحث المنهج الكيفي في هذا البحث، حيث قام بجمع البيانات من الكتب والمجلات والمقالات والرسائل، ثم قام بتحليلها. وقد توصل الباحث إلى أن إصدار الصكوك الإسلامية لتمويل التنمية الاجتماعية يسهم في تحقيق التطور الاقتصادي وزيادة صيغ التمويل الإسلامي والتنمية المالية في أفغانستان. الكلمات المفتاحية: أفغانستان، صكوك، تمويل التنمية الاجتماعية، التجربة الماليزية. Abstract This study aims to present a financing proposal that highlights the role of Sukuk as an effective tool in financing social development, including areas such as education, healthcare, and infrastructure projects. This tool contributes to enhancing economic development, creating job opportunities, and reducing poverty and unemployment. In this context, Afghanistan, being a poor country, needs to issue Sukuk to finance social development, benefiting from Malaysia’s successful experience in this field. The Malaysian experience in developing the Sukuk sector for financing social development is considered one of the most successful experiences globally, because of several factors, including government support, attracting local and international investors, the availability of a legal and regulatory framework for Sukuk, in addition to the presence of an independent Sharia supervisory body. Malaysia has issued various types of Sukuk to finance social development. The researcher employed a qualitative approach in this study, collecting data from books, journals, articles, and theses, and then analyzing it. The researcher concluded that issuing Sukuk to finance social development contributes to achieving economic progress and increasing Islamic financing modalities and financial development in Afghanistan. Keywords: Afghanistan, sukuk, social development funding, the Malaysian experience.